Female sex protects against renal edema, but not lung edema, in mice with partial deletion of the endothelial barrier regulator Tie2 compared to male sex - van Leeuwen, Anoek L. I.; Beijer, Elise; Ibelings, Roselique; Dekker, Nicole A. M.; van der Steen, Marjolein R. A.; Roelofs, Joris J. T. H.; van Meurs, Matijs; Molema, Grietje; van den Brom, Charissa E. (PloS one, 2023)
The endothelial angiopoietin/Tie2 system is an important regulator of endothelial permeability and targeting Tie2 reduces hemorrhagic shock-induced organ edema in males. However, sexual dimorphism of the endothelium has not been taken into account. This study investigated whether there are sex-related differences in the endothelial angiopoietin/Tie2 system and edema formation. Adult male and female heterozygous Tie2 knockout mice (Tie2.sup.+/-) and wild-type controls (Tie2.sup.+/+) were included (n = 9 per group). Renal and pulmonary injury were determined by wet/dry weight ratio and H&E staining of tissue sections. Protein levels were studied in plasma by ELISA and pulmonary and renal mRNA expression levels by RT-qPCR. In Tie2.sup.+/+ mice, females had higher circulating angiopoietin-2 (138%, p<0.05) compared to males. Gene expression of angiopoietin-1 (204%, p<0.01), angiopoietin-2 (542%, p<0.001) were higher in females compared to males in kidneys, but not in lungs. Gene expression of Tie2, Tie1 and VE-PTP were similar between males and females in both organs. Renal and pulmonary wet/dry weight ratio did not differ between Tie2.sup.+/+ females and males. Tie2.sup.+/+ females had lower circulating NGAL (41%, p<0.01) compared to males, whereas renal NGAL and KIM1 gene expression was unaffected. Female sex seems to protect against renal, but not pulmonary edema in heterozygous Tie2 knock-out mice. This could not be explained by sex dimorphism in the endothelial angiopoietin/Tie2 system.